Pengaruh Arang Sekam Terhadap Pertumbuhan Tanaman Seledri (Apium graveolens L.) - Desri Ahmad Dani Pohan; Widya Lestari; Khairul Rizal (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2021)
Effect of Husk Charcoal on Growth of Celery Plants (Apium graveolens L). This research was conducted in the village o-f Aek Tapa, Purwosari Hamlet, Marbau District, Labuhanbatu Regency. This research will be conducted from April to June 2020. The method used is average. Observation The parameters observed were the highest celery plant height at age. The highest average celery plant height at the age of 8 MST was obtained from the treatment of rice husk A3 300 gr / plant that is 17,8 cm while the average height of celery plant at A2 200 gr / plant that is 24,5 cm later while the average height of celery plants at A1 100 gr / plant is 18,2 cm and the average height of celery plants without treatment (Control) is 21,0 cm. The highest number of leaves (celery) of celery plants at the age of 8 MST was obtained in the treatment of rice husk A3 300 gr / plant that is 24 strands while the average number of celery leaves at A2 200 gr / plant is 20 strands later while the average number of celery leaves at A1 100 gr / plant that is 16 strands and the average number of celery leaves P0 (without treatment) is 14 strands. The highest average weight of celery plants in the highest treatment of husk charcoal obtained A3 300 gr / plant that is 23 gr while the average weight of celery plants at A2 200 gr / plant is 21 gr then while the average weight of celery plants in A1 treatment 100 gr / plant that is 15 gr and the wet weight of the celery plant in the P0 treatment (without treatment) is 12 gr. Keywords: celery, husk charcoal, vegetebles